Feed forms, feeding systems and metabolizable energy levels in diets for brown-egg laying pullets - Flavio Manabu Yuri; Amanda D’avila Verardi; Aline Félix Schneider Bedin; Jaqueline Kunhen Mayer; Clóvis Eliseu Gewehr (Ciência Rural)
ABSTRACT: Evaluated different feed forms (FF), (mash or pellets), feeding systems (FS) (ad libitum or controlled) and metabolizable energy levels (ME) (2,900 kcal/kg or 2,750 kcal/kg) in rearing period 1 (7 to 12 weeks) and 2 (13 to 17 weeks). Utilized 400 brown-egg laying pullets a completely randomized design in 2x2x2 factorial arrangement (eight treatments, with five replications). In period 1, feed intake was similar (P > 0,05) between FF and between ME, however pullets fed ad libitum showed 27.5% higher intake than fed with controlled amounts (P < 0,05). Body weight (BW) differed (P < 0.05) in the FS. Feed conversion (FC) was not affected (P > 0.05) by any of the study factors. Flock uniformity was affected (P < 0.05) by FF and by FS, with an interaction between the factors (P < 0.05). The pullets fed the mash feed ad libitum had better uniformity (P < 0.05) than the pullets fed with the controlled mash feed. The pelleted feed caused the worst uniformity. In rearing period 2, feed intake was affected (P < 0.05). That pullets fed mash or pelletized feed ad libitum consumed 8g more (P < 0.05) on average, than those in the controlled FS. In the ad libitum supply, intake was higher (P < 0.05) for the mash feed than for the pelleted feed. BW and FC were not affected by any of the factors (P > 0.05). Uniformity (%) was influenced by the mash or controlled systems (P < 0.05). Between 7 and 17 weeks of age, brown-egg laying pullets need to be fed with a mashed diet in a controlled feeding system, with 2,750 kcal/kg of metabolizable energy.